Seasonal differences in emergency department visits for scooter associated injuries. (1st February 2022) - Gudeman, Andrew; Loder, Randall T.; Figueras, Jorge; Osterbur, Todd; Fitzgerald, Ryan
ABSTRACT: Hoverboards and electric scooters have surged in popularity in the past decade. These devices carry their own injury profiles and have caused increasing emergency department visits for injury. The purpose of this study was to compare both hoverboards and electric scooters to more traditional scooters and evaluate seasonal variations in their injury patterns. The National Electronic Injury Surveillance System (NEISS) database was used, downloading cases with the appropriate consumer product codes. Four distinct scooter groups were created, and were: non-powered scooters, powered scooters, electric scooters, and hoverboards. Statistical analyses were first performed with SUDAAN software to account for the stratified and weighted nature of the data to obtain national estimates of injuries and associated demographic variables. Cosinor analyses were performed to analyze the estimated number of emergency department (ED) visits for rhythmic variation by month and weekday of injury. Weekday by month analyses were studied using a three-dimensional topographic concept. Overall, there were over 1 million ED visits over the 20 years for injuries due to the four different types of scooters (75.8% nonmotorized scooters, 12.4% motorized scooters, 6.8% hoverboards, and 2.4% electric scooters). Cosinor analyses demonstrated that there was a peak in injuries in the summer and on weekends for all scooters, except for hoverboards. For hoverboards 21% of all ED visits occurred in December, with mostly occurring exactly around Christmas Day. This study confirms previous findings that scooter injuries occur mostly in warmer months and is the first to demonstrate a topographical "Christmas Effect" of hoverboard injuries. This information can be used in health care resource allocation as well as design of potential prevention strategies.